The Problem Of Education In Children's Literature Of The National Renaissance Period - Matchonov S. (Euro Asian Journal Publishing, 2024)
This article is devoted to the interpretation of children's literature of the national renaissance period as a part of general literature, analysis of the literature of this period based on the integrity of time and space.
Keywords: educational essence of literature; folk psychology; children's literature of the independence period